2016
DOI: 10.1038/pr.2016.98
|View full text |Cite
|
Sign up to set email alerts
|

Graded oxygen saturation targets and retinopathy of prematurity in extremely preterm infants

Abstract: Background:We compared the incidence of severe retinopathy of prematurity (ROP) and need for laser treatment before and after implementing graded pulse oximeter oxygen saturation (SpO 2 ) targets in extremely preterm infants. Mortality and other secondary outcomes were compared. Methods: Before 2002, we used 90-94% as the SpO 2 target in infants 24 0/7 -27 6/7 wk gestation and birth weight <1,000 g until 35 6/7 wk postmenstrual age (PMA). We implemented graded SpO 2 targets based on vaso-obliterative and vaso-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 34 publications
1
40
0
1
Order By: Relevance
“…This is consistent with our findings. Others have suggested that a somewhat lower target could be a better balance of outcome risks 10 14 27 28. Our data would support the latter as well, if the clinical goal was to reduce the likelihood of hyperoxemia and accept a marginal increase in the likelihood of hypoxemia.…”
Section: Discussionsupporting
confidence: 72%
“…This is consistent with our findings. Others have suggested that a somewhat lower target could be a better balance of outcome risks 10 14 27 28. Our data would support the latter as well, if the clinical goal was to reduce the likelihood of hyperoxemia and accept a marginal increase in the likelihood of hypoxemia.…”
Section: Discussionsupporting
confidence: 72%
“…[30] It may also make physiologic sense to titrate SpO 2 target ranges based on individual patient characteristics, such as gestational age, postmenstrual age, and transfusion status; some have embraced this concept of a “moving target” for SpO 2 . [31]…”
Section: Discussionmentioning
confidence: 99%
“…FiO 2 will be adjusted to target oxygen saturation (SpO 2 ) from 89% to 93% in preterm infants <30 weeks GA and from 90 to 94% in infants ≥30 weeks GA by pulse oximeter [ 8 ].…”
Section: Methodsmentioning
confidence: 99%